Investigating the antidepressant effects of CBT-I in those with major depressive and insomnia disorders - Parky H. Lau; Alison E. Carney; Onkar S. Marway; Nicole E. Carmona; Maya Amestoy; Colleen E. Carney (Journal of Affective Disorders Reports, 2022)
Introduction: Cognitive behavioral therapy for insomnia (CBT-I) is a highly effective treatment for insomnia disorder that also helps with myriad clinically relevant, non-sleep specific symptoms - most notably, depression. Studies evaluating depression change after CBT-I suggest that CBT-I is an effective therapy for depression. Subsequently, empirical efforts have started investigating the mechanisms by which CBT-I exerts an antidepressant effect. The present study replicates the efficacy of CBT-I on depressive complaints and examines whether changes in sleep-specific variables predict depression outcome after CBT -I. Methods: Seventy participants presenting with comorbid insomnia and major depressive disorders (MDD-I) completed four sessions of CBT-I over eight weeks. Participants completed daily sleep diaries and self-report measures at baseline and post-treatment to assess changes in sleep and mood-related variables. Results: CBT-I was associated with large improvements in depression (d = 0.8). Tendencies to ruminate in response to fatigue predicted post-treatment depression improvements (β = 0.294). Other predictors of post-treatment mood improvement included younger age (β = -0.191) and lower baseline depression (β = -0.472). Limitations: The study was an open trial without a control group, restricting conclusions that can be made. Participants who joined the trial received insomnia-specific treatment; therefore, questions relevant to those who are primarily seeking mood treatment cannot be addressed. Discussion: The results suggest that younger MDD-I participants with moderate depression symptoms may benefit most from the antidepressant effects of CBT-I. Additionally, targeting the tendency to ruminate in response to fatigue is an important endeavor in CBT-I, as it produces depression improvement.